Utilization of Buffalo Hydrolysed Fascia in Buffalo Meat Patties - B, JagannathaRao.; K, Kondal Reddy.; Awati, Basawaraj; V. V , Kulkarni.; T , Madhava Rao. (Journal of Meat Science, 2017)
Epimysial fascia was collected from buffalo carcasses under hygienic conditions from organised slaughterhouse, was cut into thin slices, defatted,further subjected to mild drying and finally powdered in a hammer mill. The powdered fascia was subjected to enzymatic hydrolysis by suspending them in mild 0.1 N hydrochloric acid solution containing 0.1% pepsin (w/w of fascia) of1:10,000 strength for 8 hours at 37oC.The concentration of 0.1 % of pepsin used for this study was decided based on degree of hydrolysis. Physico-chemical properties like proximate principles, collagen contentand in- vitro pepsin digestibility of hydrolysed fascia weredetermined. Buffalo meat patties were prepared by replacing lean meat at 0, 10, and 20%. Replacement of lean with hydrolysed fascia did not affect proximate composition of patties except proteins. Amongst processing qualities though pH increased, the emulsion stability, shear force, cooking yield lowered.Nutritional qualities like available lysine,collagen increased significantly whereas calculated PER decreased but remained well above universally accepted index of 2.5.Texture and sensory attributes were also significantly affected but remained good to very good upto a level of 20%. Results from this study indicated that meat could be replaced up to 20% withhydrolysed fascia in patties formulations without affecting sensory qualities along with nutritional gain.
Keywords: Hydrolysed fascia; Buffalo meat; Patties; Quality